Kontruksi Prinsip Dasar Etika Profesi Akuntan: Internalisasi Karakter Pewayangan Pandawa Lima - Dinna Riyani Dinna Riyani; Lilis Ardini (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2021)
The purpose of this study is to know and understand the basic principles of accounting professional ethics, in the form of accounting professional ethics consisting of five basic principles, among others; objectivity, integrity, confidentiality and professional behavior, professional competence and prudence ,. These basic principles are internalized to the nature and character of the Five Pandavas. The five Pandavas are Yudistira, Bima, Arjuna, Nakula and Sadewa. The five Pandavas are known to have good character and values to be used as role models for life, including an accountant who runs his profession. This study uses qualitative methods and the approach used in this study is a literature study on the explanation of each basic principle of professional accountant ethics which is internalized through the Pandawa puppet show.